A dimensão comunicacional dos rolezinhos da grande Vitória : cotidiano, sociabilidade e visibilidade - Alvarenga, Angelo Bortolon de (2017)
This dissertation analyzes the daily life, the processes of sociability, with a view to some visibility, of young social actors from the outskirts of Greater Vitória. The imbrication between daily life, sociability and visibility is reflected in the phenomenon, meeting of young people from the outskirts of the urban centers, which took place in shopping malls (and eventually in other spaces) of the big cities. In this research, the object of study is characterized by the meetings held at Moxuara Shopping, located in Cariacica, a component municipality of the Greater Vitória metropolitan region. The rolls are organized by the social network Facebook, social network that composes an informational territoriality in this research, and concretized in person in said mall, geographic territoriality of that study. In this way, both territorialities are embedded functioning as a space for the effectiveness of the experience of young people. Faced with this experience, this dissertation will try to know some aspects of youth from the periphery, through the theoretical and empirical analysis of the little ones.